The economy of Roman religion - Wilson, Andrew 1968-; Ray, Nick; Trentacoste, Angela (Oxford studies on the Roman economy, 2023)
This interdisciplinary edited volume presents twelve papers by Roman historians and archaeologists, discussing the interconnected relationship between religion and the Roman economy over the period c. 500 BC to AD 350